INHIBITION OF PARAOXONASE1 BY KETONE BODIES: AN INVITRO STUDY - RICHARD S, AUSTIN; J M D’SOUZA, CLETUS (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: In uncontrolled diabetes mellitus, concentration of ketone bodies is elevated to up to 25mM. This study aims to investigate the inhibitory action of ketone bodies on paraoxonase and arylesterase (ARE'ase) activity of Paraoxonase1 (PON1). Method: The inhibition of PON1 by ketone bodies was determined spectrophotometrically by using paraoxon and phenyl acetate as substrates. Result: Acetone decreased 32% of paraoxonase activity and 23% of ARE'ase activity. Sodium-3-hydroxybutyrate showed 20 % reduction in paraoxonase activity but it did not affect ARE'ase activity. In contrast, neither of the enzyme activities was affected by sodium acetoacetate. Conclusion: Higher concentration of acetone and sodium-3- hydroxybutyrate contribute to the reduction of PON1 activity. Keywords: Paraoxonase1, Arylesterase, High density lipoprotein, Ketone bodies, Sodium -acetoacetate, Acetone, Sodium-3-Hydroxybutyrate.